Découverte de Guizotia abyssinica (L.f.) Cass. (Asteraceae) en Algérie et mise au point sur son utilisation - Rebbas, Khellaf; Benhissen , Saliha; Sarri , Djamel; Belkassam , Abdelouahab; Bounar , Rabah (Algerian Journal of Biosciences, 2022)
Guizotia abyssinica (L. f) Cass. (Asteraceae) is native to Ethiopia. This asteracea was discovered in the region of Sétif and M’sila, in northeastern Algeria. Ecological notes are also provided.